Defending the four principles approach as a good basis for good medical practice and therefore for good medical ethics. Issue 1 (16th December 2014) - Gillon, Raanan
Abstract : This paper argues that the four prima facie principles—beneficence, non-maleficence, respect for autonomy and justice—afford a good and widely acceptable basis for 'doing good medical ethics'. It confronts objections that the approach is simplistic, incompatible with a virtue-based approach to medicine, that it requires respect for autonomy always to have priority when the principles clash at the expense of clinical obligations to benefit patients and global justice. It agrees that the approach does not provide universalisable methods either for resolving such moral dilemmas arising from conflict between the principles or their derivatives, or universalisable methods for resolving disagreements about the scope of these principles—long acknowledged lacunae but arguably to be found, in practice, with all other approaches to medical ethics. The value of the approach, when properly understood, is to provide a universalisable though prima facie set of moral commitments which all doctors can accept, a basic moral language and a basic moral analytic framework. These can underpin an intercultural 'moral mission statement' for the goals and practice of medicine.